SISTEM REKRUTMEN TENAGA PENDIDIK DALAM UPAYA MENINGKATKAN MUTU PENDIDIKAN DI SMA MUHAMMADIYAH 2 BANDAR LAMPUNG - Anggia, Rifka Ayu; Patimah, Siti; Bedi, Fisman; Ayu, Sovia Mas; Junaidah, Junaidah (STKIP Pesisir Selatan, 2024)
The Human Resources (HR) management system used must be in accordance with the needs of the organization, so that the recruitment process is not just filling employee vacancies or just getting ordinary HR, but highly dedicated and professional HR in their fields. The purpose of writing is to examine and analyze further how the teaching staff recruitment system in improving the quality of education carried out at SMA Muhammadiyah 2 Bandar Lampung. The method of writing this scientific article uses a qualitative method. Data is obtained through observation, where the researcher functions as an instrument to make observations, in-depth interviews with primary data sources and study documentation. The results of the educator recruitment process at SMA Muhammadiyah 2 Bandar Lampung are: Recruitment implementation, The series of new educator recruitment activities at SMA Muhammadiyah 2 Bandar Lampung develops according to the needs of the school and always learns from the experience of recruiting previous educators. The school forms a team to recruit the required educators, then distributes e-flyers or announcements to attract applicants or educators through social media such as Facebook, Instagram, Tiktok, WhatsApp, and websites with Muslim or Muslimah qualifications, love the world of education, able to work with the team, minimum education S1 according to major.